2020
DOI: 10.1002/oby.22912
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Artemisia scoparia’s Anti‐Inflammatory Activity in Cultured Adipocytes, Macrophages, and Pancreatic β‐Cells

Abstract: Objective An ethanolic extract of Artemisia scoparia (SCO) improves adipose tissue function and reduces negative metabolic consequences of high‐fat feeding. A. scoparia has a long history of medicinal use across Asia and has anti‐inflammatory effects in various cell types and disease models. The objective of the current study was to investigate SCO’s effects on inflammation in cells relevant to metabolic health. Methods Inflammatory responses were assayed in cultured adipocytes, macrophages, and insulinoma cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In addition, there are abundant data showing anti-inflammatory actions of SCOPA in cultured cell lines relevant to metabolic function. In lipopolysaccharide (LPS)-stimulated RAW 246.7 murine macrophages, an ethanolic SCOPA extract, previously found to attenuate lipolysis and markers of adipose tissue inflammation, also inhibited the expression of several inflammatory genes ( 72 ). In this same cell line, a different ethanolic extract reduced nitric oxide (NO) production in cells treated with LPS and interferon gamma (IFNγ) ( 53 ), while a methanolic extract from a third source failed to inhibit NO release from LPS-treated RAW 264.7 cells ( 63 ).…”
Section: Effects Of a Scoparia On Determinants Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are abundant data showing anti-inflammatory actions of SCOPA in cultured cell lines relevant to metabolic function. In lipopolysaccharide (LPS)-stimulated RAW 246.7 murine macrophages, an ethanolic SCOPA extract, previously found to attenuate lipolysis and markers of adipose tissue inflammation, also inhibited the expression of several inflammatory genes ( 72 ). In this same cell line, a different ethanolic extract reduced nitric oxide (NO) production in cells treated with LPS and interferon gamma (IFNγ) ( 53 ), while a methanolic extract from a third source failed to inhibit NO release from LPS-treated RAW 264.7 cells ( 63 ).…”
Section: Effects Of a Scoparia On Determinants Of ...mentioning
confidence: 99%
“…Comparable effects of SCOPA have been observed in the THP-1 human monocyte cell line, undifferentiated 3T3-L1 murine preadipocytes, and in the HMC-1 human mast cell line ( 69 , 73 ). Moreover, reduced pro-inflammatory NF-κB promoter activation in IL-1β-treated pancreatic beta-cells, which are also vulnerable to obesity-related inflammation, has been observed in response to SCOPA ( 72 ). Taken together, these data from multiple models and treatment conditions clearly indicate that SCOPA is a potent anti-inflammatory agent and that it can antagonize inflammation in conditions consistent with metabolic dysregulation.…”
Section: Effects Of a Scoparia On Determinants Of ...mentioning
confidence: 99%
“…Interestingly, an agonist of PPARγ, an ethanolic extract of Artemisia scoparia (SCO), showed both in-vitro and in-vivo beneficial effects on insulin sensitivity and adipocyte function [ 30 ]. Impaired adipocyte differentiation, moreover, is also associated with inflammatory processes in the adipose tissue that are well-known pathogenetic aspects of obesity [ 31 ]. Furthermore, SCO seems to interfere with the inflammatory pathway, thus reducing metabolic dysfunction, and has a favorable effect on pancreatic β-cells [ 31 ].…”
Section: Resveratrol and Obesity: Possible Mechanisms Of Actionmentioning
confidence: 99%
“…Impaired adipocyte differentiation, moreover, is also associated with inflammatory processes in the adipose tissue that are well-known pathogenetic aspects of obesity [ 31 ]. Furthermore, SCO seems to interfere with the inflammatory pathway, thus reducing metabolic dysfunction, and has a favorable effect on pancreatic β-cells [ 31 ]. Therefore, the investigation on the possible combined effects of resveratrol and SCO on adipogenesis and adipose tissue metabolism could represent an interesting challenge for the future.…”
Section: Resveratrol and Obesity: Possible Mechanisms Of Actionmentioning
confidence: 99%
“…Artemisia scoparia Waldst.et Kit, a perennial plant in the Asteraceae family, grows on sandy beaches and is known to possess anti-inflammatory and antioxidant effects (22)(23)(24). Although natural products each have their own health benefits, several studies have been reported that show synergistic effects when they are used as a mixture (25,26).…”
Section: Introductionmentioning
confidence: 99%